(untitled) (Journal of the College of Basic Education, 2022)
The research aimed to identify: 1-The level of post-formal thinking of intermediate school students 2- The differences in the level of post-formal thinking of intermediate school students according to the gender variable (males – females) 3-The differences in the level of post-formal thinking of intermediate school students for the two grades (first – third). The sample consisted of (200) male and female students in the intermediate schools in the center of Al-Qadisiyah Governorate for the first and third grades average from the morning study, for the academic year (2020-2021) they were chosen by random stratified method, on the basis of equal distribution .To achieve the objectives of the research, the researcher built a scale of Post-formal thinking of intermediate school students and relied on the theory of the inherent feature as a theoretical basis in building the scale, as it identified the theoretical definition of the concept of post-formal thinking, which consisted of three domains and developed a definition for each domain and derived items from these definitions in proportion to each of these domains consistent with the nature of the society that will apply the scale, which consists of (36) items in its final form, after verifying the psychometric properties of the scale, the reliability was extracted using the Cronbach’s alpha coefficient whose value was (0.88), and after completing the construction of the tool it was applied to the research sample . SPSSused in data processing, and the research concluded that intermediate school students have the ability to think beyond formalism, and there are no significant differences between them. Satiya at the level (0.05) in post-formal thinking according to the gender variable (males - females) and not according to the grade variable (first – third)